Sistem Informasi Penjualan pada UD . NEW SEHATI Pacet Mojokerto - Noviana Masita; A.B. Tjandrarini; Pantjawati Sudharmaningtyas (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
UD. New Sehati is small and medium entreprises (SME) which stand since January 2000. This SME move in production and sell many kinds of chips. The sell activity in UD. New Sehati begin from registration of stock product, registration sells, order, retur, barter and report which is connected sells. The problem happened is indispline ini registration administration sells, management income, order which directly to owner which is not written by employee, registration flow stock product, retur, and barter, with doesn’t have report which connected sells. The solution to solve problem is made information system which can made to save the master data is needed. Registration stock product in warehouse and shop, registration transaction is happened, history from the registration and manage that data become the report which connected sells to make easier the owner to do control and evaluation, with can take the decision to make bisnis strategy in entreprise. The conclusion result of test and try which has done information system this sell is produce result nineteen (19) report with connected sells which can used by the owner as subject for evaluation to take decision and make strategy of business in entreprises.